Clients, clinics and social justice: Reducing inequality (and embedding legal ethics) via an LLB portfolio pathway. Issue 3 (2nd July 2018) - Collinson, Robert; Diver, Alice; McAvoy, Sharon
Abstract : Purpose: The purpose of this paper is to present a case study of an innovative, three-module pathway designed by the Department of Law and Criminology at Edge Hill University (England) in 2014. In addition to supporting the work of its campus pro-bono law clinic, the first-two modules aim to enhance and evidence the legal skills of EHU's undergraduate LLB students, to embed a deeper awareness of the (legal) ethics needed for sustainable legal practice (within PRME), and to highlight the increasing need for socially responsible advocates, able to defend the rights of marginalised, vulnerable clients. Design/methodology/approach: The critical analysis of the content and scope of an innovative, work-based learning LLB module pathway, which furthers the aim of the UN Global Compact and the PRME, and ties them firmly to socio-legal issues and advocacy involving recent jurisprudence. Findings: The case law used within the modules, and the practical work of the students in the campus law clinic, are relevant to social justice issues and to the promotion of PRME values—they promote awareness of human rights principles, highlight the importance of access to legal services and provide students with knowledge of legal ethics. Enhanced employability skills flow from this. Research limitations/implications: This is a narrow case study but still provides a useful analysis of an innovative, PRME relevant module pathway. The model mirrors international trends in clinical legal education and also offers a template for other law schools keen to promote the concept of ethical, just legal practice. Practical implications: The paper posits that enhanced employability can flow from real world tasks such as advocacy for marginalised or disadvantaged groups and presents an exemplar for other law schools wishing to embed ethics/clinical law practice into their curriculum. Social implications: The paper highlights how the campus law clinic serves the public in a deprived region—it raises awareness of human rights and of social justice issues. It has the potential to feed into litigation on social welfare issues (housing, social security, child welfare, etc.). Originality/value: The discussion of the human rights case law that is used in the Year 2 "bridging module" (which prepares students for working in the law clinic in their final year) is particularly relevant and is analysed in detail, highlighting how this module pathway is aimed at promoting PRME and UN Global Compact principles.